2003
DOI: 10.2135/cropsci2003.3700
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Improvement of Agronomic Traits of Winter Wheat Cultivars Released in France from 1946 to 1992

Abstract: In a context where agricultural practices in Europe are likely to go toward extensive systems with lower inputs, it is important to determine the genetic improvement of winter wheat (Triticum aestivum L.) not only in high‐input agricultural systems but also in low‐input systems. This study assesses the improvement in agronomic traits of winter wheat cultivars cultivated in France during the second half of the 20th century at four agronomic treatments: two levels of fungicide were combined with two levels of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
157
4
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(188 citation statements)
references
References 20 publications
(32 reference statements)
24
157
4
3
Order By: Relevance
“…The greater variability of aerial and root biomass found within semi-dwarf cultivars when compared with tall ones supports the statement that genetic variability was not reduced in modern Mediterranean durum wheat cultivars as a consequence of the breeding activities conducted during the 20th century . The significant differences observed in the greenhouse between cultivars carrying the Rht-B1a (tall) and Rht-B1b (semi-dwarf) allele for aerial and root biomass indicated that the dwarfing allele not only reduced above-ground biomass, as widely reported by previous studies (Brancourt-Hulmel et al 2003;Royo et al 2007;Álvaro et al 2008a), but also caused a decrease in total root biomass and in each root section. Moreover, the reduction caused by the dwarfing allele in root biomass (ca.…”
Section: Aerial and Root Biomass In The Greenhousesupporting
confidence: 75%
“…The greater variability of aerial and root biomass found within semi-dwarf cultivars when compared with tall ones supports the statement that genetic variability was not reduced in modern Mediterranean durum wheat cultivars as a consequence of the breeding activities conducted during the 20th century . The significant differences observed in the greenhouse between cultivars carrying the Rht-B1a (tall) and Rht-B1b (semi-dwarf) allele for aerial and root biomass indicated that the dwarfing allele not only reduced above-ground biomass, as widely reported by previous studies (Brancourt-Hulmel et al 2003;Royo et al 2007;Álvaro et al 2008a), but also caused a decrease in total root biomass and in each root section. Moreover, the reduction caused by the dwarfing allele in root biomass (ca.…”
Section: Aerial and Root Biomass In The Greenhousesupporting
confidence: 75%
“…A number of field studies have compared yield trends of an historical time-series of wheat varieties (31,32,33). Although these studies suffer from the same confounding factors as comparable studies with rice, the wheat evaluations were more rigorous because yield gains were quantified with and without fungicide protection against diseases and at different levels of N fertilization.…”
Section: Estimating Trends In Yield Potential Of Maize and Wheatmentioning
confidence: 99%
“…As acurácias seletivas dos caracteres avaliados oscilaram entre 0,87 e 0,98, e indicaram boa precisão experimental (Resende & Duarte, 2007 Cormier et al (2013). Esse resultado deve-se ao aumento significativo (p≤0,01) no índice de colheita de N (Figura 2), ao longo dos anos e em todas as doses de N avaliadas (Brancourt-Hulmel et al, 2003). Os valores de ICN estiveram entre 50 e 80%, variação semelhante à observada por Barraclough et al (2010) e Gaju et al (2011).…”
Section: Resultsunclassified
“…Com doses baixas, a EAN explica a maior parte da resposta observada em EUN (Ortiz-Monasterio et al, 1997;Foulkes et al, 1998;Le Gouis et al, 2000), enquanto que, em doses altas, destaca-se a importância da EUtN (Brancourt-Hulmel et al, 2003). Entretanto, não há consenso entre os diferentes estudos, pois tanto a EAN quanto a EUtN podem contribuir para o incremento da EUN (Barraclough et al, 2010;Le Gouis et al, 2010;Gaju et al, 2011).…”
Section: Introductionunclassified